Iconographic Veneration of St. Gregory Palamas in the Late Byzantine and Post-Byzantine Period - Ribolov, Svetoslav (Forum Theologicum Sardicense, 2025)
Svet. Ribolov, Iconographic Veneration of St. Gregory Palamas in the Late Byzantine and Post-Byzantine Period. The study covers a wide range of sources that provide information about the remembrance of St. Gregory Palamas after the fall of Constantinople and its submission to the Ottoman rule (1453). Moreover, the article examines various iconograph-ic models, which visually present the liturgical veneration of the Saint in Mount Athos, Thessalonike, Beroia and Kastoria. In these regions, unlike elsewhere, the veneration of Palamas has been preserved throughout the Ottoman period. It should also be mentioned that the research is integral and interdisciplinary by its nature, as it combines liturgical, historical, dogmatic and iconographic material. The aim of the study is to provide a realistic picture of the influence of the veneration of Palamas on the liturgical life and theological activity during the Ottoman era in the canonical territories of the Ecumenical Patriarchate and the Archbishopric of Ohrid.